Electric vehicle charging load prediction considering the orderly charging. (December 2022) - Tian, Jiang; Lv, Yang; Zhao, Qi; Gong, Yucheng; Li, Chun; Ding, Hongen; Yu, Yu
Abstract: The prediction of the orderly charging load of electric vehicles is of great significance for planning of charging facilities, analysis of bearing capacity of the distribution network and later rectification and reconstruction. This article proposes a method of charging load prediction based on characteristics of EV charging behavior and nonlinear programming. This article uses Monte Carlo algorithm to predict charging probability and disorderly charging load of EVs, and uses non -linear programming algorithm to solve the optimized target function of orderly charging to achieve the prediction of the orderly charging load of EVs in the region.